Using a Dielectric Capacitance Cell to Determine the Dielectric Properties of Pure Sand Artificially Contaminated with Pb, Cd, Fe, and Zn - Mohammed Dahim; Musab Abuaddous; Rabah Ismail; Hashem Al-Mattarneh; Aiman Jaradat (Applied and Environmental Soil Science)
This paper presents a new method of dielectric capacitance cell as a proposed device for measuring the impedance of pure sand artificially contaminated with four heavy metals. Dielectric constant and loss factor of clean and contaminated sand at various levels were calculated from the measured sand impedances. The advantages and benefits of using the proposed dielectric capacitance cell were its low cost, simple calculation, calibration procedures, portable and lightweight, and easy to modify the electrodes to suit testing in the field. Pure sand was saturated with water artificially polluted in the lab with Pb, Cd, Fe, and Zn at heavy metal contents 0, 7.5, 15, 22.5, and 30 mg/kg of sand. The dielectric properties of polluted sand were evaluated at a frequency range from 100 kHz to 1000 kHz. The polluted sand exhibit different dielectric constants and loss factors from the unpolluted sand. The results also indicate that the dielectric constant decreases with increasing pollution level for all heavy metals. This may attribute to the polarization mechanism change with existing heavy metal. The loss factor of sand increases with the increasing pollution level. This may be explained by the increase of ionic conductivity of pore water with heavy metal in the sand. Sand polluted with heavy metal with higher resistivity and density possess a higher dielectric constant and lower loss factor than other polluted metals. Evaluation of the dielectric characteristics of polluted sand could have the potential to monitor heavy metal pollution. Even with promising results obtained with the proposed dielectric device, it is necessary to explore several other factors affecting the measurements such as sand water content, soil texture, and type of soil. Also, testing polluted soil near industrial pollution is needed.